Metallo-stannosilicate heterogeneous catalyst for biodiesel production using edible, non-edible and waste oils as feedstock. Issue 4 (August 2018) - da Silva, Danilo Antonio; Santisteban, Oscar A.N.; de Vasconcellos, Adriano; Silva Paula, Alex; Aranda, Donato A.G.; Giotto, Marcus Vinicius; Jaeger, Christian; Nery, José G.
Graphical abstract: Highlights: Stannosilicate was synthesized and characterized by XRD, SEM and solid-state MAS NMR. XRD and solid-state MAS NMR revealed a structure of OPT metallosilicate. The material was applied as heterogeneous catalyst for biodiesel production. FAMEs or FAEEs yields higher than 90.0% using refined edible and non-edible oils. FAEEs yield of 96.6% was obtained by the conversion of refined microalgae oil. Abstract: This study reports the synthesis, physicochemical characterization by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and solid-state MAS NMR ( 1 H, 23 Na, 29 Si and 119 Sn MAS NMR) of a metallo-stannosilicate and its application as a heterogeneous catalyst for biodiesel production via ethanolysis and methanolysis routes using edible, non-edible an waste oils as feedstocks. XRD characterization of the metallo-stannosilicate has revealed a typical structure of mixed octahedral-pentahedral-tetrahedral material with an orthorhombic unit cell (a = 14.522 Ǻ, b = 12.469 Ǻ, and c = 10.654 Ǻ). 119 Sn single-pulse MAS NMR results presented two resonance lines, at δ1 = -683.8 ppm and δ2 = -690.9 ppm, which were assigned to the tin octahedrally coordinated in the metallo-stannosilicate structure. Heterogenous catalytic studies in the transesterification of refined edible, non-edible, and waste oils have resulted in high yields of FAMEs and FAEEs (fatty acid methyl and ethyl esters), nevertheless the highest FAMES (98.2%) and FAEEs (96.6%) yields were obtained for non-edible microalgae oil extracted from the genetically modified heterotrophic algal strain Prototheca moriformis . Catalytic studies also using non-edible macaw palm oil ( Acrocomia aculeata ) with a high content of free fatty acids (FFAs) demonstrated that the catalyst could simultaneously perform esterification and transesterification reactions. These findings indicate the potential application of this novel metallo-stannosilicate in the production of renewable and environmentally clean biofuels, like biodiesel, using different sources of lipids feedstocks, notably those that do not compete with food production.